2007
DOI: 10.1088/0953-8984/19/17/176228
|View full text |Cite
|
Sign up to set email alerts
|

Spin–flip transition of L10-type MnPt alloy single crystal studied by neutron scattering

Abstract: Magnetic structure, tetragonality, and the spin-flip transition for an L1(0)-type MnPt ordered alloy were studied by neutron scattering using a single-crystal specimen. Tetragonality of the lattice showed strong correlation with the spin-flip transition. Although the spin-flip transition looks like a gradual change of the easy axis in the temperature range between 580 and 770 K, two modes of magnon-gap peaks with different energies were observed in this transition temperature range. Thus, the crystal consists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 10 publications
4
19
0
Order By: Relevance
“…The obtained values of lattice parameters and magnetic moments of MnPt and FePt magnetic ground states are in good agreement with the corresponding experimental data [8][9][10][11][22][23][24] and previous first-principles calculations. [25][26][27][28][29][30][31][32][33][34][35][36] Pt atoms are found to have either small ͑0.39 for MnPt, 0.34 for FePt for Model 3͒ or negligible magnetic moments ͑Models 1 and 2͒.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The obtained values of lattice parameters and magnetic moments of MnPt and FePt magnetic ground states are in good agreement with the corresponding experimental data [8][9][10][11][22][23][24] and previous first-principles calculations. [25][26][27][28][29][30][31][32][33][34][35][36] Pt atoms are found to have either small ͑0.39 for MnPt, 0.34 for FePt for Model 3͒ or negligible magnetic moments ͑Models 1 and 2͒.…”
Section: Discussionsupporting
confidence: 89%
“…Such a small value for MnPt explains the experimentally observed controversy and sensitivity of the MCA to changes in composition and temperature. [8][9][10][11] Besides, being small, the out-of-plane MCA of MnPt is sensitive to the details of first-principles calculations. 26 The out-of-plane MCA of FePt is in good agreement with previous first-principles calculations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For these two models we practically obtained the same residuals, which shows that we are not able to determine the moment direction within the tetragonal ab plane. It has been reported that MnPt exhibits two different magnetic structures [30]. At high temperatures above 750 K, the Mn moment lies in the basal plane whereas it undergoes a spin-flip transition in a broad temperature region ranging from 750 to 570 K, leading to a magnetic structure with Mn moments aligned parallel to the tetragonal c axis.…”
Section: Mn2ptpdmentioning
confidence: 99%